Strategi Komunikasi Kominfo Jatim dalam Penguatan Literasi Digital Melalui Program Cerdas Digital (CERDIG) - Tira Fitriawardhani; Julyanto Ekantoro; Theresia Abigial Tanya Pradana (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This study explores the communication strategy employed by the East Java Provincial Office of Communication and Informatics (Kominfo Jatim) in strengthening digital literacy through the Cerdas Digital (CERDIG) Program. Using a descriptive qualitative approach, data were collected through in-depth interviews and documentation. The analysis draws on Harold Lasswell’s communication model, which examines the communicator, message, media, audience, and effect. The findings reveal that Kominfo Jatim develops clear and educational digital literacy messages and delivers them through diverse channels such as training sessions, webinars, and social media campaigns. CERDIG successfully reaches various target groups, including civil servants, students, communities, and persons with disabilities. The program contributes to improving public understanding of key digital literacy pillars, namely digital skills, digital safety, digital ethics, and digital culture. The study concludes that well-structured communication strategies, tailored to audience needs and supported by appropriate media, enhance the effectiveness of digital literacy initiatives. Overall, CERDIG plays a significant role in promoting a more informed, critical, and responsible digital society in East Java.